Heterospecific detection of host alarm cues by an inquiline termite species (Blattodea: Isoptera: Termitidae). (October 2016) - Cristaldo, Paulo F.; Rodrigues, Vinícius B.; Elliot, Simon L.; Araújo, Ana P.A.; DeSouza, Og
Abstract : Termite inquilines specialize on living in and feeding on a host termite nest. However, the mechanisms allowing survival of two mutually hostile populations confined to a single nest are not understood. Here we report on inquiline termites that respond to their host's alarm cues. Upon detecting these cues, the inquilines do not join in with the host's nest defence, but use this information for their own benefit, to escape danger. Using behavioural bioassays under laboratory conditions, we show that the obligatory inquiline Inquilinitermes microcerus (Termitidae: Termitinae) responds both to its own alarm signal and to alarm cues from its host, Constrictotermes cyphergaster (Termitidae: Nasutitermitinae). Conversely, this host responded only to its own alarm signal. Despite perceiving their host's alarm cues, inquilines were never observed sharing nest defence with their host in experimentally damaged nests in the field. We argue that this allows inquilines not only to minimize encounters and hence conflict with their hosts, but also to use their host alarm information to escape the host's enemies, which are also likely to be enemies of the inquilines. Our results show a new benefit that inquilines gain from the host, and we discuss the inquiline way-of-life from an evolutionary perspective, as the outcome of constraints and benefits imposed by living in host nests. Highlights: Do termite inquilines detect their host's alarm cues? We tested hosts' vs inquilines' responses to conspecific/heterospecific alarm cues. Inquilines, but not hosts, recognized and responded to heterospecific cues. Inquilines did not join in with the host's nest defence efforts.